2020
DOI: 10.1038/s41598-020-75449-z
|View full text |Cite
|
Sign up to set email alerts
|

Effect of physical parameters and temperature on the piezo-electric jetting behaviour of UV-curable photochromic inks

Abstract: Although resource-efficient processes like inkjet printing have a large potential to foster the development of smart and functional textiles, one bottleneck still is the development of functional inks. To make inkjet printing and UV curing given production techniques for smart and functional specialty products, e.g. photochromic textiles, deepened knowledge about the development, rheological behavior and jetting behavior of functional ink is needed. This paper focuses on the formulation and performance of UV-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(1 citation statement)
references
References 42 publications
0
0
1
Order By: Relevance
“…It is commendable to specify that the effect of temperature on the surface tension of the ink formulations containing APSV is neglected as of exceptional little changes beyond four cycles. Other than that, the visual examination revealed that the increase in temperature has no thinning effect on the different ink formulations, contrasted to other data recently investigated (Seipel, Yu and Nierstrasz, 2020). Furthermore, the sudden temperature change has not occurred any aggregation of pigment particles in the formulated inks, which is not found to agree with the work reported by Nasar et al (2011).…”
Section: Freeze/thaw Cycling Stabilitycontrasting
confidence: 85%
“…It is commendable to specify that the effect of temperature on the surface tension of the ink formulations containing APSV is neglected as of exceptional little changes beyond four cycles. Other than that, the visual examination revealed that the increase in temperature has no thinning effect on the different ink formulations, contrasted to other data recently investigated (Seipel, Yu and Nierstrasz, 2020). Furthermore, the sudden temperature change has not occurred any aggregation of pigment particles in the formulated inks, which is not found to agree with the work reported by Nasar et al (2011).…”
Section: Freeze/thaw Cycling Stabilitycontrasting
confidence: 85%